Predictors of Place of Death for those in Receipt of Home-Based Palliative Care Services in Ontario, Canada. Issue 2 (June 2015) - Guerriere, Denise; Husain, Amna; Marshall, Denise; Zagorski, Brandon; Seow, Hsien; Brazil, Kevin; Kennedy, Julia; McLernon, Robin; Burns, Sheri; Coyte, Peter C.
Many cancer patients die in institutional settings despite their preference to die at home. A longitudinal, prospective cohort study was conducted to comprehensively assess the determinants of home death for patients receiving home-based palliative care. Data collected from biweekly telephone interviews with caregivers (n=302) and program databases were entered into a multivariate logistic model. Patients with high nursing costs (odds ratio [OR]: 4.3; confidence interval [CI]: 1.8–10.2) and patients with high personal support worker costs (OR: 2.3; CI: 1.1–4.5) were more likely to die at home than those with low costs. Patients who lived alone were less likely to die at home than those who cohabitated (OR: 0.4; CI: 0.2–0.8), and those with a high propensity for a home-death preference were more likely to die at home than those with a low propensity (OR: 5.8; CI: 1.1–31.3). An understanding of the predictors of place of death may contribute to the development of effective interventions that support home death.